SOCIAL RETURN ON INVESTMENT (SROI) ANALYSIS OF THE ELECTRIC MOTOR CONVERSION TRAINING PROGRAM IN NORTH LAMPUNG - Redaputri, Appin Purisky; Barusman, M Yusuf S (EnviroScienteae, 2024)
Converting conventional motors into electric vehicles can reduce dependence on fossil fuels. The conversion process involves engine replacement, charging system installation, and vehicle structure modification. The conversion program was carried out involving workshops and vocational high school students. The Social Return on Investment (SROI) method was employed to measure the social and economic impacts of the program, involving impact identification, measurement, monetization, cost comparison, and analysis. The PLN Cares program undertook motor conversion with the aim of improving sustainability and quality. The research problem and objectives focused on measuring the SROI in the electric motor conversion program. The research method employed a qualitative approach with data collection techniques through in-depth interviews, focus group discussions, observations, and literature studies. Data were continuously analyzed during and after collection. SROI calculations involved initial investment capital input and impact value, resulting in an SROI ratio of 5.03. The research results indicated that the PLN Cares program had a significant social impact, with an SROI ratio indicating a profitable investment value. Conclusions and recommendations involved maintaining the working mechanisms, synergy among stakeholders, and using the program as a guide for similar projects in the future.